Silodosin improves pain and urinary frequency in Bladder Pain Syndrome/Interstitial Cystitis patients - Beatriz Margarida Araújo da Silva (2022)
Introduction: Bladder Pain Syndrome/Interstitial Cystitis (BPS/IC) is a chronic inflammatory disease with complaints of suprapubic pain, associated with other lower urinary tract symptoms (LUTS) as increased frequency, nocturia and persistent urge to void. Increasing evidence suggests that stress plays a crucial role in a subgroup of BPS/IC patients. Experimental data indicate that stress enhances the excitability of bladder nociceptors and increases ATP release from urothelial cells through the stimulation of alpha1A-adrenoceptors. With this in mind, we aimed to assess the efficacy, tolerability, and safety of a daily dose of silodosin in refractory BPS/IC patients and its correlation with stress coping. Material & Methods: An open-label trial was conducted with 20 refractory BPS/IC female patients. Patients were evaluated at baseline at the 8th and 12th weeks. The primary endpoint was bladder pain measured by a 1-10 VAS. Secondary endpoints included daily frequency, nocturia and maximal voided volume obtained from a 3-day bladder diary, OSS for symptoms and problems, the QoL question from IPSS and two questions accessing stress coping. After baseline evaluation, patients started a daily dose of 8mg silodosin, which could be titrated to 16mg at week 8. Results are shown in median values with percentiles 25 and 75 (25; 75). Wilcoxon signed-rank test was used for comparisons. A MID of 3 points for pain, 2 voiding episodes for frequency and 1 for nocturia were established to define clinically relevant improvement. Adverse events were assessed. Results: The median age of the patients was 56 (46; 66) years old. Four patients requested dose escalation to 16mg at week 8. Three dropouts occurred before week 8. The median pain score decreased from 8.00 (6.00; 8.00) at baseline to 4.00 (2.00; 5.50) (p<0001), meaning the primary endpoint was reached. Concerning secondary endpoints, total daily urinary frequency decreased from 14.00 (13.00; 21.00) to 9.00 (7.50; 11.00), and maximal voided volume increased from 175.00 (150.00; 250.00) ml to 250.00 (200.00; 350.00)ml (p<0.05). All the other secondary endpoints also showed a statistically significant improvement at end of treatment compared to baseline. Of the 17 patients, 11 had a ≥ 3 point improvement in pain, meaning that 65% of patients reached the MID of clinical significance; 14 (82%) decreased 2 or more episodes in daily frequency. Fifteen women related bladder symptoms with stress levels, and the capacity to cope with stress was low. Conclusions: Silodosin can be an effective, well-tolerated, treatment for refractory BPS/IC in women whose symptoms are aggravated with stress and who express difficulty coping with stress.